Optimizing Collaborative Learning as A Solution to Overcome Math Anxiety in Mathematics Learning: A Systematic Literature Review - Ningtyas, Syahratu Cahya; Sari, Yurizka Melia (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
Mathematics anxiety is one of the obstacles experienced by students in the learning process and has an impact on decreased motivation and academic achievement. This study aims to examine the role of collaborative learning as a solution to overcome mathematics anxiety. This study uses a Systematic Literature Review (SLR) approach with data collection through the SINTA and Google Scholar databases. Based on the established inclusion and exclusion criteria, six relevant scientific articles published between 2019 and 2025 were identified. The results of the study indicate that collaborative learning models such as Problem-Based Learning, Teams Games Tournament (TGT), Student Teams Achievement Division (STAD), Group Investigation, Fan-N-Pick, and Heroe's consistently reduce students' math anxiety levels. The commonality among these models lies in creating an active, enjoyable learning environment that supports positive social interaction among students. By encouraging students' emotional and intellectual engagement, collaborative learning has proven effective in enhancing self-confidence and mathematical concept understanding. Therefore, optimizing the implementation of collaborative learning tailored to students' characteristics is recommended as a pedagogical strategy to improve the quality of mathematics education and reduce learning anxiety across various educational levels.